Caracterização de polimorfismos e atividade de enzimas relacionadas ao estresse oxidativo em linhagens bacterianas tolerantes ao herbicida mesotrione - Becher, Stela (2009)
Mesotrione, 2-(4-Mesyl-2-nitrobenzoyl)-1,3-cyclohexanedione, is a trycetone herbicide chemical class, with high leaching potential, and competitively inhibit 4-hydroxyphenylpyruvate dioxygenase (HPPD), that converts tyrosine to plastoquinone and α-tocopherol, and was found in plants, fungus, and bacteria, including Acinetobacter. The aim of this work was to characterize pathways of Brazilian strains of Acinetobacter facing mesotrione. Acinetobacter calcoaceticus and Acinetobacter sp. were selected in up to 15.00 mM (resistance) and 0.03 mM (tolerance) concentrations of mesotrione and tested at 35 mM buffered solution in spectrophotometry until 60 hours, showing to be incapable to degrade mesotrione. Computer bacterial cells measures (ImageJ 1.37v) indicate starvation process, probably due to non use of mesotrione as carbon source, and this characteristic could be consider a marker for herbicide degradation. Mesotrione herbicide activity is major in N, and enhanced by S, and has a strong electron withdrawing. For this reason, we studied antioxidative stress enzymes catalase, superoxide dismutase and glutathione reductase, by SDS-PAGE, non-denaturatig PAGE and spectrophotometry. Acinetobacter calcoaceticus showed a higher response to oxidative stress than Acinetobacter sp., with more soluble proteins and lower number of electrophoresis bands isoforms (12 against 23), because its enzymes were selected for this herbicide and show better adaptation than Acinetobacter sp.. A microbial strategy of herbicide resistance/tolerance and specific oxidative stress raised by mesotrione herbicide could give additional non-degradating options to microorganisms, not necessarily leading to fast herbicide degradation, so determining the herbicide fate in soils and groundwater.